Validasi Sebaran Kapal Penangkap Ikan Tradisional Menggunakan Data Penginderaan Jauh Dan GPS Tracker - Suniada, Komang Iwan (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018)DO - 10.24843/jmas.2018.v4.i01.14-21, 2017)
Utilization of radar satellite data to monitoring vessels distribution in regard to combating IUU fishing is a newly developed in Indonesia. Ship detection using radar satellite data performed with high accuracy which is about 79% to the size of the boats between 24-81 meters (averaging 45 meters).  However, information about accuracy of the radar satellites to detect small traditional fishing vessel are not yet widely available, and making this study is very important to conducted.    The research was conducted at the west part of Belitung Island waters using RADARSAT-2 satellite data to detect vessels distribution which was acquired by radar ground station Perancak at October 25, 2016 and also using vessel position data which is acquired by using GPS tracker.  There are 10 traditional fishing vessel was used as a sample, in accordance with the availability of GPS tracker.  All vessels are made from wood with the size between 11 to 15 meter and using ‘bubu’ as a primary fishing gear to catch fish.  Accuracy test was done using overlay analysis between vessel distribution information resulted from radar image analysis with the vessel position data coming from the GPS Tracker.  Result showed that the accuracy of radar data on extended high incidence beam mode to detect the distribution of traditional fishing vessels with small size (11-15 meters) is about 30% and over estimate measuring between 7.5 to 8 meters.